The Impact of E-Accounting on Mexican Accounting Firms - Roberto Rodríguez Venegas (European Scientific Journal, ESJ, 2017)
In the global economy electronic accounting, or e-accounting, is defined as any accounting system which is based on information communication technology for the capture and processing of a business’ financial data. E-accounting relies mainly on computers, although it may be used on other devices. In Mexico, the concept of electronic accounting has been widened by adding the obligation to send the tax authorities the information resulting from its application. The objective of this study was to describe the impact of electronic accounting on accounting firms, as well as establish the relationship between the factors of change and compliance with the new regulations, including information submission deadlines. We applied a questionnaire to 90 accounting firms through a study of four factors: the demographic profile of the firm, the demographic profile of the general director, investment in software and training, as well as the reasons for using electronic accounting in relation to the level of compliance. The results show that the model as a whole is significant and that the investment in software and training, as well as the legal structure of the firm, are relevant factors for implementation.